2018
DOI: 10.1016/j.rmed.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-microbiological analysis of 121 patients with pulmonary Mycobacteroides abscessus complex disease in Japan – An NTM-JRC study with RIT

Abstract: Rationale: No comprehensive analysis has previously been performed to evaluate the clinical aspects of and microbiological evidence associated with Mycobacteroides abscessus complex (MABC) infection in a region, such as Japan, with a low MABC incidence. Objectives: This study aimed to clarify the clinicopathological characteristics of MABC, which included clinical relatedness to erm(41) sequevar, phenotype (as colony morphology and minimum inhibitory concentration), and genotype. Methods: A total of 121 MABC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
2
17
1
Order By: Relevance
“…The number of incident MABC-PD cases has recently increased consistent with the nationwide survey data, and exceeded that of MK-PD cases. The proportions of M. abscessus and M. massiliense in this study were 57% and 43%, respectively; the proportions were similar to those found in other reports from Japan [15,19,20]. Similar to the report of the national surveillance, the mean age of pulmonary TB cases increased during the study period [8].…”
Section: Discussionsupporting
confidence: 89%
“…The number of incident MABC-PD cases has recently increased consistent with the nationwide survey data, and exceeded that of MK-PD cases. The proportions of M. abscessus and M. massiliense in this study were 57% and 43%, respectively; the proportions were similar to those found in other reports from Japan [15,19,20]. Similar to the report of the national surveillance, the mean age of pulmonary TB cases increased during the study period [8].…”
Section: Discussionsupporting
confidence: 89%
“…Multiple NTM species isolates are not rare. A previous report on M. abscessus complex (MABC) disease showed that approximately 25% of the patients had multiple NTM species, and 80% of them met the microbiological diagnostic criteria for non-MABC NTM disease (16). Our results showed some clinical characteristics for patients with multiple NTM species and several species-dependent characteristics in the patterns of co-isolation.…”
Section: Discussionsupporting
confidence: 60%
“…For example, M. intracellulare disease had a more severe clinical presentation and poorer treatment outcomes when compared with M. avium disease in one study [36]. Additionally, compared with M. abscessus disease, M. massiliense disease responds more favourably to macrolide-containing antibiotic therapy [18,37,38]. In this context, our data clearly showed that the accurate identification of the species or subspecies of the aetiological NTM organism is very important in the prognosis of NTM-PD.…”
Section: Discussionmentioning
confidence: 62%